2023
DOI: 10.2478/ers-2023-0023
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the performance of the agricultural sector in Hungary due to the 2008 economic crisis and COVID-19 pandemic

Enikő Lencsés,
Szilárd Hegedűs,
Norbert Bajkó

Abstract: Subject and purpose of work: The paper examines two of the most important sectors of agriculture, crop and livestock production, in a time series analysis. The authors analyzed the number of enterprises, the number of employees, labor costs, turnover, and balance sheet total, and also assessed the evolution of liquidity and profitability in the two sectors, broken down by size. Materials and methods: The results of livestoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…They preferred certain returns over high return spice crops. Small farms often struggle to maintain longterm viability due to their failure to reinvest profits into the business, prompting the need for a change in their ownership approach (Lencsés et al, 2023), because they do not have enough profit to reinvest in agriculture to increase their farm productivity. Furthermore, cost-benefit analysis showed that the spice crops were more profitable than traditional crops in Haryana state.…”
Section: Efektywność Marketingowamentioning
confidence: 99%
“…They preferred certain returns over high return spice crops. Small farms often struggle to maintain longterm viability due to their failure to reinvest profits into the business, prompting the need for a change in their ownership approach (Lencsés et al, 2023), because they do not have enough profit to reinvest in agriculture to increase their farm productivity. Furthermore, cost-benefit analysis showed that the spice crops were more profitable than traditional crops in Haryana state.…”
Section: Efektywność Marketingowamentioning
confidence: 99%